Respiratory, Cardiac, and Neuropsychiatric Manifestations of Postacute Sequelae of Coronavirus Disease 2019 in Lima, Peru - Rahman, Rifat S. (2023)
Background: Few studies have examined the burden of postacute sequelae of coronavirus disease 2019 (COVID-19) (PASC) in low- and middle-income countries. We sought to characterize PASC with self-reported questionnaires and clinical examinations of end-organ function in Lima, Peru. Methods: From January to July 2021, we recruited participants at least 8 weeks after COVID-19 diagnosis from a case registry in Lima, Peru. We evaluated participants for PASC with questionnaires, neuropsychiatric evaluations, chest X-ray, spirometry, electrocardiogram, and echocardiogram. We used multivariable models to identify risk factors for PASC. Results: We assessed 989 participants for PASC at a median 4.7 months after diagnosis. Clinically significant respiratory symptoms were reported by 68.3% of participants, particularly those who had been severely ill during acute COVID-19, and were associated with cardiac findings of ventricular hypertrophy or dilation on echocardiogram. Neuropsychiatric questionnaires were consistent with depression in 20.7% and cognitive impairment in 8.0%. Female sex and older age were associated with increased risk of respiratory (adjusted odds ratio [aOR], 2.36 [95% confidence interval CI, 1.69-3.31] and aOR, 1.01 [95% CI, 1.00-1.03], respectively) and neuropsychiatric sequelae (aOR, 2.99 [95% CI, 2.16-4.18] and aOR, 1.02 [95% CI, 1.01-1.03], respectively). Conclusions: COVID-19 survivors in Lima, Peru, experienced frequent postacute respiratory symptoms and depression, particularly among older and female participants. Clinical examinations highlighted the need for cardiopulmonary rehabilitation among persons with severe COVID-19; psychosocial support may be required among all COVID-19 survivors.